An Archaeology of the Street: A Cinegraphic Analysis of Streets in Urbino, Italy - Blizard, Mark (Enquiry The ARCC Journal for Architectural Research, 2013)
This article presents the issues, questions, and discoveries of an experimental design studio, conducted in Urbino, Italy during spring semester of 2013. Utilizing high definition video cameras and their digital ecosystem of hardware and software, the students focused on uncovering the identity, or genetic code, of the street by examining its spatial and temporal extension. An archaeological method composed of traditional spatial analysis, typological studies, and cataloging of elements provided the initial framework for a cinegraphic inquiry. What emerged was a sense that the street was an urban artifact––a place itself rather than merely a conduit or path between places––whose spatial and temporal characteristics informed our perception of the city. The street, perhaps only understood in our movement through its sequential elements and spaces, seems critical in shaping the city's identity. Traditional means of analysis by themselves are limited in that they only isolate fragments of a much more complex whole. Throughout the inquiry, we found that the digital analytical methods that were employed and the digital tools themselves provided new insight into the analytical process while expanding our understanding of the street and its relationship to the landscape and the larger urban fabric of Urbino. By extension, cinegraphic analysis may contribute to our ability to uncover the qualities and structure that constitute the identity of a city, or any place.